Snow-cover loss attenuates the effects of N addition on desert nutrient cycling and microbial community - Yang, Yaru; Liu, Weiguo; Adams, Jonathan M.; Song, Bin (Frontiers in Plant Science, 2023)
Desert ecosystems are sensitive to nitrogen (N) deposition. Considering snow is an important source of soil water, which is vital for plant growth and the biogeochemical cycle in desert areas. The effects of N deposition on biological soil crusts (BSCs) could be impacted by the removal of snow-cover. Here, we established a split-plot experiment in the Gurbantunggut Desert to examine the effects of snow-cover treatments on soil nutrients, enzyme activities, and the bacterial community under various N addition. The removal of snow-cover reduced the soil nutrients with light and moderate N addition, it also reduced the activities of urease (URE) and alkaline phosphatase (PHOS). The structural equation model (SEM) result indicated that low soil moisture (SMO) under snow-uncover inhibited the bacterial community, particularly suppressed bacterial diversity. Additionally, N addition indirectly affected the bacterial community via modifications to soil nutrients, and soil organic matter (SOM) (P < 0.001) was the crucial factor. Snow-uncover weakened soil nutrient and enzyme responses to N addition, indicating that snow-cover removal reduced the sensitivity of the desert ecosystem to N deposition. The study highlights the critical role of snow-cover in the desert ecosystem, raising our awareness of the ecological risks of BSCs in future global change.